Analisis Daya Dukung Lingkungan terhadap Pengembangan Wisata Alam Semongkat di Kecamatan Batulanteh Kabupaten Sumbawa - Fahrianto, M Said; Sukardi, Lalu; Wahyuningsih, Endah (Jurnal Silva Samalas, 2026)
The Semongkat Nature Tourism Park (TWA) in Batulanteh Subdistrict, Sumbawa Regency, is a nature conservation area with great potential to be developed into a tourist destination; however, an increase in visitor numbers risks putting pressure on environmental quality if not balanced by an appropriate carrying capacity analysis. This study aims to analyze environmental carrying capacity, assess the feasibility of potential natural tourist attractions (ODTWA), and formulate a development strategy for the Semongkat TWA area. The study employed a combination of quantitative and qualitative methods involving 100 respondents selected using the Slovin formula, including analyses of physical, actual, and effective carrying capacity, an assessment of the feasibility of natural tourist attractions, and a SWOT analysis. The results show that the area’s effective carrying capacity reaches 18,852 tourists/day, far exceeding the actual average daily visitation of only 347–395 tourists equivalent to 1.8–2.1% of the optimal capacity. The ODTWA feasibility index of 78% indicates a “feasible” category, while the area’s internal and external positions fall within the “aggressive growth” quadrant, directing strategies toward strengthening environmental and cultural educational tourism, hygiene and safety protocols, forest rehabilitation, and integrated marketing efforts with the village government. These findings indicate that the Semongkat TWA can still be developed gradually without exceeding its carrying capacity, as long as physical constraints such as slope gradient and soil susceptibility to erosion remain the primary guidelines for development. Substantively, these findings also support the achievement of the Sustainable Development Goals (SDGs), particularly Goal 8, 12, 15 through nature tourism development that remains within the environmental carrying capacity.